EVALUATION OF A TWO-STAGE TREATMENT OF DOMESTIC SEWAGE WITH ANAEROBIC-AEROBIC MICROBIAL FILM - A.Mesdaghinia (Tehran University of Medical Sciences, 1986)
The objective of this research was to study the feasibility of a two stage continuous system employing anaerobic-aerobic microbial film for domestic wastewater treatment and the effect of iron on the behavior of sulfate reducing bacteria in anaerobic metabolism. A bench scale system with an anaerobic filter followed by aerobic fixed units used plastic media and was operated in up flow manner with hydraulic detention times of 6 hours, whereas the aerobic unit utilized diffused aeration. Raw domestic sewage was fed to the anaerobic unit, and the aerobic unit was fed with the anaerobic unit was fed with the anaerobic effluent. Although, the anaerobic filter did not show a considerable organic removal with domestic sex age it was improved when glucose was added to the influent to increase influent soluble COD. When glucose was added the anaerobic filter removed about 290 mg/1 of influent soluble COD. The aerobic unit produced an excellent effluent with COD, BOD5 and TSS concentrations of 37 mg/1, 9 mg/1 and 10 mg/l respectively. Overall, the system removed 95 percent of influent COD, 97 percent of influent BOD5 and 96 percent of influent TSS.